Pertanggungjawaban Direksi dan Komisaris dalam Kepailitan berdasarkan Prinsip Pierching The Corporate Veil - Mohammad Choirul Anam (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2021)
This study aims to analyze assistance regarding the application of the principle of veil piercing to the Directors and Commissioners of the Company according to Law Number 40 of 2007 concerning Limited Liability Companies for bankruptcy work. This legal research uses juridical normative legal research which is descriptive analytical with a conceptual approach and an invited approach. Legal materials techniques use library research (library research) and are analyzed using qualitative analysis. Based on the results of the research, it shows that the enforcement violates the corporate veil, to protect the rights of shareholders for actions carried out by company organs such as Directors and commissioners who act not in accordance with company objectives. In carrying out their duties, the Board of Directors and commissioners must be based on good faith, caution and a sense of full responsibility towards the company. If the Board of Directors and Commissioners are negligent in carrying out their duties, resulting in the bankruptcy of the company. Directors and Commissioners may be subject to the principle of penetrating the corporate veil, namely personal liability to the personal assets of the Directors and Commissioners for losses incurred by the company and shareholders. This principle is used to protect the interests of the company and shareholders from actions that could harm the company by the Directors and CommissionersKeywords—: Pierching the Corporate Veil’s Principles; Responsibility; Directors; Commissioners; Bankruptcy.